Hoveyda‐Type Quinone‐Containing Complexes – Catalysts to Prevent Migration of the Double Bond under Metathesis Conditions. Issue 3 (23rd January 2017) - Kajetanowicz, Anna; Milewski, Mariusz; Rogińska, Joanna; Gajda, Roman; Woźniak, Krzysztof
Abstract : Three new quinone‐containing Hoveyda‐type complexes have been synthesised and fully characterised. Their ability to suppress undesired double‐bond migration along the carbon chain during metathesis reactions was examined. It was proved that these catalysts decrease the amounts of undesired side‐products with a shifted double bond in the reaction mixture. Abstract : Olefin metathesis – how to avoid migration of the double bond? The synthesis and suppression of undesired double‐bond migration along the carbon chain during metathesis reactions with three quinone‐containing Hoveyda‐type complexes as catalysts is presented. It has been proved that these catalysts decrease the amounts of undesired side‐products with a shifted double bond in the reaction mixture.